Finally a director-general : WTO at the crossroads - Randhawa, Dipinder Singh (2021)
Dr Ngozi Okonjo-Iweala’s election as the WTO’s new director-general was confirmed after President Biden cleared the hurdle placed by the previous Trump administration. But Okonjo-Iweala faces the toughest challenges since the inception of the world trade body.